2022
DOI: 10.1038/s41598-022-14850-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis and phenotyping of walnut seedling roots under nitrogen stresses

Abstract: Nitrogen is an essential core element in walnut seedling growth and development. However, nitrogen starvation and excessive nitrogen stress can cause stunted growth and development of walnut seedlings, and environmental pollution is also of concern. Therefore, it is necessary to study the mechanism of walnut seedling resistance to nitrogen stress. In this study, morphological and physiological observations and transcriptome sequencing of walnut seedlings under nitrogen starvation and excess nitrogen stress wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The function of RVE genes in roots has rarely been reported before. Recently, transcriptome analysis of Juglans regia and Medicago truncatula found that RVE genes may be involved in the nitrogen metabolic pathway [ 50 , 51 ]. Moreover, RVE genes had diverse expression patterns in different developmental stages of jujube fruit [ 52 ], and PbRVE1b promoted anthocyanin accumulation in P. bretschneideri peel [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The function of RVE genes in roots has rarely been reported before. Recently, transcriptome analysis of Juglans regia and Medicago truncatula found that RVE genes may be involved in the nitrogen metabolic pathway [ 50 , 51 ]. Moreover, RVE genes had diverse expression patterns in different developmental stages of jujube fruit [ 52 ], and PbRVE1b promoted anthocyanin accumulation in P. bretschneideri peel [ 29 ].…”
Section: Discussionmentioning
confidence: 99%